Ontología Dialéctica em Hegel - Marra Rodrigues, Osvaldino (Nómadas. Critical Journal of Social and Juridical Science, 2010)
Hegel was the last philosopher to explain the philosophy as a system. Initiator, even before Heidegger and Gadamer, hermeneutics. Critical Kant showed that the presence of two parallel worlds is just an illusion of reason too wedded to the sacredness of the thing itself. Hegel has shown, long before Heidegger, to be time and have an ontological overlap, the horizon of Dasein is on course to be the same, and that as history unfolds, and that "going up and down that is the same. For the Phenomenology of Spirit shows that the path of consciousness that rises to the Absolute, traveled seriously, pain, patience and the work of the negative (PhG, § 9) is both Ontology and Science.
Keywords: Hegel; Dialectic; Ontology